Generic reclassification of species formerly included in Rhantus Dejean (Coleoptera, Dytiscidae, Colymbetinae) - BALKE, MICHAEL; HÁJEK, JIŘÍ; HENDRICH, LARS (Zootaxa, 2017)
A reclassification of several species traditionally included in Rhantus Dejean, 1833 is given: Nartus Zaitzev, 1907 is re-instated as genus with one species in the Nearctic and one in the Palaearctic region; two new genera are erected: Meri-diorhantus n. gen., with M. antarcticus (Germain, 1854) n. comb., M. calidus (Fabricius, 1792) n. comb., M. limbatus (Aubé, 1838) n. comb., M. orbignyi (Balke, 1992) n. comb., M. validus (Sharp, 1882) n. comb. in the Neotropical region (M. calidus also in the southern USA and along the eastern coast as far north as New York City), and the monotypic Caperhantus n. gen., with C. cicurius (Fabricius, 1787) n. comb. in south Africa. Furthermore, nine Pacific and Australian Rhantus are transferred to the genus Carabdytes Balke, Hendrich & Wewalka, 1992: C. alutaceus (Fauvel, 1883) n. comb., C. guadalcanalensis (Balke, 1998) n. comb., C. monteithi (Balke, Wewalka, Alarie & Ribera, 2007) n. comb., C. novaecaledoniae (J. Balfour-Browne, 1944) n. comb., C. oceanicus (Balke, 1993b) n. comb., C. pacificus (Boisduval, 1835) n. comb., C. plantaris (Sharp, 1882) n. comb., C. poellerbauerae (Balke, Wewalka, Alarie & Ribera, 2007) n. comb. and C. pseudopacificus Balke, 1993b) n. comb. All changes are based on a previous comprehensive molecular phylogenetic analysis of Colymbetinae. Diagnostic characters are given for all genera mentioned above and each of them is illustrated with one or more habitus pictures. An updated key to all genera of Colymbetinae is also given.